If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -3x = c Solving X + -3x = c Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '3x' to each side of the equation. X + -3x + 3x = c + 3x Combine like terms: -3x + 3x = 0 X + 0 = c + 3x X = c + 3x Simplifying X = c + 3x
| 7(n-12)= | | 72=-6k | | -63=-3x | | 4c^2+12c+9= | | 2y=-48 | | 25r^2+90rt+81t^2= | | -8x+7y-x-6y+4x= | | -15+4g=-39 | | 16s^2-72s+81= | | 2x-23=835 | | 36w^2-49= | | 56=2x | | 25x^2-55x+30=0 | | 12h^2-17hj-5j^2= | | 2y-9=13 | | x-361-195+1236-22=599 | | 3x+5=x-5 | | 5v^2+21v-20= | | -72=-5(n+6)-7 | | x-152+419=794 | | 20v^3+105v^2-100v= | | 6x=8+7x | | 20=4(x+7) | | 4y+8=16 | | 3x-2x+8-10=7 | | 10+x=28 | | -4x-4+x-2y+7x= | | 2=3(x+7)+2 | | 4-(7n-5)+18n=5(5n+1) | | 25=-3k+5(k+7) | | 2x+3=19+5x | | x^2-0.3=-0.06x |